Mappings and decompositions of continuity on almost Lindelöf spaces - A. J. Fawakhreh; A. Kiliçman (International Journal of Mathematics and Mathematical Sciences, 2006)
A topological space X is said to be almost Lindelöf if for every open cover {Uα:α∈Δ} of X there exists a countable subset {αn:n∈ℕ}⊆Δ such that X=∪n∈ℕCl(Uαn). In this paper we study the effect of mappings and some decompositions of continuity on almost Lindelöf spaces. The main result is that a image of an almost Lindelöf space is almost Lindelöf.